Culpable crimes - Ruiz Ramal, Ariana (2011)
In culpable crimes, it is necessary to carefully distinguish actual or potential knowledge of the danger that the conduct creates for legal rights, from abstract knowledge of the duty of care. Knowledge of the danger caused is effective in conscious or represented guilt, but is potential in unconscious or unrepresented guilt. When this knowledge is effectively lacking and is not enforceable, the culpable typicity will be lacking, but when this is not the case, but rather the subject is directly unaware of his duty of care in an abstract way, it cannot be expected that he recognizes the concrete unlawfulness of his conduct and reproach him for not having been aware of it, even though he is perfectly aware of the danger that it introduces, which would set up a clear assumption of a direct error of prohibition.